Answered

Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Explore thousands of questions and answers from knowledgeable experts in various fields on our Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

First term: 2 3/4 sixth term: 3 7/12 what is the rule

Sagot :

Answer:

we conclude that the rule will be:

[tex]a_n=\frac{31}{12}+\frac{1}{6}n[/tex]

Step-by-step explanation:

Given

[tex]a_6=3\frac{7}{12}=\frac{43}{12}[/tex]

[tex]a_1=2\frac{3}{4}=\frac{11}{4}[/tex]

We know the arithmetic sequence with the common difference is defined as

[tex]a_n=a_1+\left(n-1\right)d[/tex]

where a₁ is the first term and d is a common difference.

so

a₆ = a₁ + (6-1) d

substituting a₆ = 43/12 and a₁ = 11/4 to determine d

[tex]\frac{43}{12}=\:\frac{11}{4}\:+\:5d[/tex]

switch sides

[tex]\frac{11}{4}+5d=\frac{43}{12}[/tex]

subtract 11/4 from both sides

[tex]\frac{11}{4}+5d-\frac{11}{4}=\frac{43}{12}-\frac{11}{4}[/tex]

[tex]5d=\frac{5}{6}[/tex]

Divide both sides by 5

[tex]\frac{5d}{5}=\frac{\frac{5}{6}}{5}[/tex]

[tex]d=\frac{1}{6}[/tex]

as

a₁ = 11/4

[tex]d=\frac{1}{6}[/tex]

Therefore, the nth term of the Arithmetic sequence will be:

[tex]a_n=a_1+\left(n-1\right)d[/tex]

substituting d = 1/6 and a₁ = 11/4

[tex]a_n=\frac{11}{4}+\left(n-1\right)\frac{1}{6}[/tex]

    [tex]=\frac{11}{4}+\frac{1}{6}n-\frac{1}{6}[/tex]

    [tex]=\frac{31}{12}+\frac{1}{6}n[/tex]

Therefore, we conclude that the rule will be:

[tex]a_n=\frac{31}{12}+\frac{1}{6}n[/tex]

Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.